DAYA TARIK OBJEK WISATA AL-JAMI’ AIR TIRIS KABUPATEN KAMPAR - Hidayatullah, Muhammad Zikri; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the description of the attractiveness and efforts to increase the attractiveness of the Al-Jami' Air Tiris Mosque tourist attraction, Kampar Regency. Kampar Regency is nicknamed the Land of Verandas of Mecca. Another nickname given to the district whose capital is Bangkinang City is Bumi Sarimadu which upholds cultural values, customs and religion in its daily life. The Jamik Air Tiris Mosque is a religious tourist attraction in Kampar Regency which was built in 1901 AD on the initiative of a great cleric named Datuk Engku Mudo Sangkal. This mosque is located on the banks of the Kampar river, precisely at the Usang Air Tiris Market. Sources were obtained through interviews, observation and documentation. Based on the research results, the conclusion of this research is that the attraction of the Jami' Air Tiris Mosque, Kampar Regency, which was built during the Dutch colonial period, is divided into history and the building itself. Keywords: Kampar Regency, Al-Jami' Air Tiris Mosque